MALATHION INDUCED MORPHOBEHAVIOURAL CHANGES IN PANTALA FLAVESCENS FABR. (ODONATA : LIBELLULIDAE) - BHARDWAJ, A.C.; TYAGI, NEELAM (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
An impact of malathion on morphobehavioural vicissitudes in Pantala flavescens Fabr. has been evaluated at various concentrations. The study has revealed loss of ability to fly, acute dorsoventral abdominal convulsions, forward forewings deflection, clockwise cyclic rotation of the dragon-fly assignificant symptoms. All the derangements have been found pesticide concentration dependent with shortest mortality period under 0.5% analathion stress was 15 minutes.